1998
DOI: 10.2307/3579858
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry Measurements of Subsets of T, B and NK Cells in Peripheral Blood Lymphocytes of Atomic Bomb Survivors

Abstract: Previous studies of blood cells from atomic bomb survivors have shown that frequencies of chromosome aberrations and somatic mutations are elevated in heavily exposed survivors and that T-cell functions and the number of mature T cells are decreased in the survivors who were exposed to radiation as adults. Current progress in flow cytometry allows a sophisticated analysis of various subsets of T, B and NK cells. In the present study, proportions of such subsets in peripheral blood lymphocytes from atomic bomb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 39 publications
5
42
1
Order By: Relevance
“…In a previously reported study, the B-cell proportion was observed to increase in A-bomb survivors who were heavily exposed to radiation (40), although the number of subjects (N ¼ 411) was much smaller than in the current study and the metabolic profiles of the subjects were not considered. A limitation of the current study may thus involve the heterogeneity of the peripheral B-cell population, which was not considered.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In a previously reported study, the B-cell proportion was observed to increase in A-bomb survivors who were heavily exposed to radiation (40), although the number of subjects (N ¼ 411) was much smaller than in the current study and the metabolic profiles of the subjects were not considered. A limitation of the current study may thus involve the heterogeneity of the peripheral B-cell population, which was not considered.…”
Section: Discussionmentioning
confidence: 79%
“…A limitation of the current study may thus involve the heterogeneity of the peripheral B-cell population, which was not considered. Radiation exposure and metabolic status may differentially influence distinct B-cell subpopulations (5,40,41), i.e., immature or mature B cells and functionally different subsets of B cells, such as follicular (conventional), marginal zone and B-1 B cells. Therefore, a potential way to clarify the biological significance of the interactions observed in this study would be to assess a more diverse subset of B cells, as specific subsets may prove to be more closely associated with radiation exposure or metabolic profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Significant decreases in naïve T cells have been observed in atomic bomb survivors [67]. The decreased proportion of CD4 + naïve T cells were attributed to reduced T cell responses to mitogens and proliferation [68]. By contrast, TQ supplementation ameliorated the decrease in the proportions of CD4 + and CD8 + T cells following exposure to gamma-irradiation.…”
Section: Discussionmentioning
confidence: 84%
“…Dose-related variations in T cell and B-cell populations in Japanese atomic-bomb survivors suggest that radiation may harm the immune system [34] at doses > 1.5 Gy, implying that whole-body or RBM dose might be the most relevant to the radiation effects of the associated systems. Although other evidence implicates infections and the immune system in cardiovascular disease [19,35,36], the negative findings of two randomized-controlled trials of antibiotic administration [37,38] suggest that bacterial infection is not likely involved in circulatory disease.…”
Section: Discussionmentioning
confidence: 99%